Protection and Certainty of Social Welfare Law in the Concept of a Welfare State: Perspective of State Administrative Law - Mohamad Fasyehhudin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The intervention of the state administration in providing legal protection and certainty for social welfare insurance is very important. However, there are still problems occurring in society, including acts of discrimination against accessing social needs, causing social inequality. The goal of this research is to determine how the government's responsibility in implementing social welfare is to provide legal protection and certainty to the community in the concept of a welfare state from the standpoint of state administrative law and how Arrangements for Social Welfare Policy Based on Government Regulation of the Republic of Indonesia Number 39 of 2012 Concerning Implementation of Social Welfare This research method is normative-juridical. The results of this study show that the responsibility and authority of the government in implementing social welfare and carrying out the duties of executive power must be based on the will of the state, which is based on statutory regulations established by the legislature. The policies regulated in the Government Regulation of the Republic of Indonesia Number 39 of 2012 concerning the Implementation of Social Welfare are rehabilitation policies, social security policies, social empowerment policies, social protection policies, infrastructure standard policies, community participation policies, registration procedures policies, and policies for institutions that organize social welfare